Impact resistance of CFRP-reinforced wood beams under axial force using a digital image correlation method. (1st April 2021) - Liu, Wen; Yu, Ying; Zhang, Zhengxiang; Liu, Chengyang; Tong, Yu
Abstract: Drop-weight testing provided data on the dynamic impact–resistance properties of wood beams reinforced with carbon fiber reinforced polymers (CFRPs) and of unreinforced plain wood beams. Axial force was also applied on the beams to improve the impact-resistance ability of the beams. The digital image correlation (DIC) technique was used to obtain impact deformation. The test results of beam failure modes, impact force–time history curve, and impact deformation were used to analyze the impact-resistance properties. In addition, the impact strength and energy dissipation of wood beams under impact load were calculated. The results indicated that reinforcement has an obvious effect on the impact-resistance ability of wood beams and that the axial force has some reinforcing effect. The strengthening effect increases in the order of 1-ply CFRP sheet, CFRP plate, and 2-ply CFRP sheet.